ФАУНА ПОЛУЖЕСТКОКРЫЛЫХ (Heteroptera) ПУСТЫНЬ КАЗАХСТАНА (Experimental biology, 2015)
305 species of Heteroptera were identified in desert zone of Kazakhstan. In relation to zoogeography dominating species are Turan, Iran–Turan and Tethys.
Keywords: desert zone of Kazakhstan; Heteroptera